The Impact of The Special General Election Judiciary on The Authority of The Constitutional Court - Lobubun, Muslim; Anwar, Iryana (Jurnal Hukum Caraka Justitia, 2022)
This study aims to analyze the establishment of a special general election Judiciary and to analyze if the special Judiciary can take over the constitutional court’s authority in handling the electoral disputes without going through changes to Article 24-C of the 1945 Constitution especially paragraph 1. The approach applied in order to answer the problems and objectives of this research was a normative juridical approach. This study employed several approaches to legal issues including the Statutory Approach, the Conceptual Approach, and the Historical Approach. The results of this study explain that although it has been mandated in Article 157 paragraph (1-2) of Law No. 10 of 2016 on a special general election Judiciary. However, the constitutional court’s authority is still well-maintained until the 2024 general elections or amendments to Article 24-C to such an extent that it concerns electoral disputes. The constitutional authority cannot be transferred immediately to the Special Courts according to Articles 156 and 157 of Law No. 10 of 2016 because there is no amendment to Article 24-C. Therefore, the constitutional court’s authority is still well-maintained until the special court is regulated by a special law.